THE SOCIAL FUNCTION OF CODE MIXING FOUND IN POEMSBYWA'S INSTAGRAM CAPTION - Ni Kadek Winasih Ni Kadek Winasih (Journal of Humanities, Social Science, Public Administration and Management (HUSOCPUMENT), 2022)
The aim of this study is to identify the social function of code switching found in poemsbywa’s Instagram caption. The data of this study was taken from poemsbywa’s instagram account. The study was conducted by using observation method in order to obtain detail information. This study were analyzed qualitatively by using theory from Troike (1982:68). The finding show that from 7 types of social function according to the theory, there are only 3 social functions of code mixing occurs in this instagram caption, they are as ideological statement, as solidarity and as direct situation. From the whole data it can be mentioned that there were 3 data classify as solidarity function, 1 data as Ideological statement function and 1 data as Direct Quotation function. Solidarity function dominantly occurred in this study.